2008
DOI: 10.1160/th08-04-0243
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar whole blood rotation thromboelastometry (Rotem) profile in 40 sideropenic anaemia patients

Abstract: The ROtation ThromboElastoMetry analyser (ROTEM, Pentapharm, Munich, Germany) is useful for studying whole blood (WB) clot formation and lysis. Reduction of haematocrit (HCT) has been reported to influence traditional thromboelastography parameters without compromising "in vitro" blood coagulation. We performed this case-control study to evaluate ROTEM profiles in sideropenic anaemia patients with different degrees of reduction of HCT levels. Forty consecutively referred patients with sideropenic anaemia were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 25 publications
5
57
3
Order By: Relevance
“…Earlier research has shown that anemia is associated with increased (thrombelastometrically measured) clot firmness [45][46][47]. Thus, our finding is in line with these resultsbut also novel as our study demonstrates for the first time and in a multivariate analysis that the analogy, i.e., that lower clot firmness is associated with higher hemoglobin concentration, is also true.…”
Section: Discussionsupporting
confidence: 91%
“…Earlier research has shown that anemia is associated with increased (thrombelastometrically measured) clot firmness [45][46][47]. Thus, our finding is in line with these resultsbut also novel as our study demonstrates for the first time and in a multivariate analysis that the analogy, i.e., that lower clot firmness is associated with higher hemoglobin concentration, is also true.…”
Section: Discussionsupporting
confidence: 91%
“…Two BD vacutainer tubes (Becton-Dickinson, Franklin Lakes, New Jersey) containing sodium citrate 109 mmol/L (3.8 % sodium citrate) and one BD vacutainer tube containing ethylenediaminetetraacetic acid 5.4 mg (EDTA) were collected from each participant for each time interval. For each test considered in the study, normal values were those obtained in a group of 40 healthy volunteers matched with cases for gender and age (±3 years), randomly selected from our database and in part previously published [17]. Hemoglobin levels, platelet count and traditional coagulative parameters (i.e., PT/INR, aPTT, fibrinogen and antithrombin) were performed according to the standard procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Given some differences, both assays are particularly useful for the evaluation of fibrinogen deficiency, factor XIII deficiency, hemophilia, and fibrinolytic state. 11,30,[87][88][89] In patients with major trauma, early diagnosis and treatment of coagulopathy may be feasible using ROTEM-guided (goal-directed) hemostatic therapy ( fig. 5).…”
Section: Hemostasis Monitoring For Massive Hemorrhagementioning
confidence: 99%
“…100 However, this finding has been questioned 101 and may reflect in vitro effects of decreased hematocrit. 89,102,103 Transfusion of erythrocytes is performed to improve oxygen carrying capacity, but increased hematocrit may also be beneficial for hemostasis. In the arterial vessel, platelets are preferentially distributed near the vessel wall (margination) because of the red cell mass.…”
Section: Initial Volume Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation